2008
DOI: 10.1143/apex.1.123001
|View full text |Cite
|
Sign up to set email alerts
|

Noise-Enhanced Sensing of Light and Magnetic Force Based on a Nonlinear Silicon Microresonator

Abstract: Microresonators with mechanical nonlinearity are applied to sensing based on the noise-enhanced stochastic transition of the vibration amplitude in bistable mechanical systems at resonance. Noise-enhanced stochastic transitions can amplify a signal in a nonlinear system. It was found that 100-nm-thick single-crystalline silicon resonators exhibit mechanical nonlinearity with both negative and positive nonlinear coefficients, depending on the vibration frequency at large vibration amplitudes. It was demonstrate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
12
0

Year Published

2010
2010
2019
2019

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(12 citation statements)
references
References 18 publications
0
12
0
Order By: Relevance
“…Previously studied systems include a parametrically driven electron in a Penning trap 2 , a superconducting loop with a Josephson junction 3 and an atomic cloud in an magneto-optical trap 4 . Micromechanical doubly clamped beams and torsional resonators driven into bistability can also exhibit noise-induced switching, leading to an enhancement of the Signal-to-Noise Ratio (SNR) [5][6][7][8] . In torsional oscillators, the nonlinearity arises from the externally applied electrostatic driving force 6,7 .…”
mentioning
confidence: 99%
“…Previously studied systems include a parametrically driven electron in a Penning trap 2 , a superconducting loop with a Josephson junction 3 and an atomic cloud in an magneto-optical trap 4 . Micromechanical doubly clamped beams and torsional resonators driven into bistability can also exhibit noise-induced switching, leading to an enhancement of the Signal-to-Noise Ratio (SNR) [5][6][7][8] . In torsional oscillators, the nonlinearity arises from the externally applied electrostatic driving force 6,7 .…”
mentioning
confidence: 99%
“…In case of a relative weak (sub-threshold) force additional noise is required to move the system from state '+c' (right) to '−c' (left). A strong force will not require the presence of added noise, as the corresponding co-energy function contains only one global The total electromechanical behaviour of the slider is described by the co-energy function given in (10). To evaluate this expression, several parameters, like the spring constant k and capacitive parameter C 0 , need to be determined experimentally.…”
Section: B Energy Functionmentioning
confidence: 99%
“…In the optical domain, SR was implemented by Palonpon et al [9] to measure weak transmittances. Ono et al [10] showed that SR can be used for sensing light and magnetic forces using a nonlinear silicon microresonator. To enhance energy harvesting, SR was applied by McInnes et al [11], by adding periodic forcing to a vibrationally excited energy harvesting mechanism enhancing the available power from their device over a mechanism without periodic forcing and only exploiting environmental noise.…”
Section: Introductionmentioning
confidence: 99%
“…Similarly, mechanical resonators that are strongly driven can show stochastic switching between two stable attractors [17][18][19] . This can potentially improve the transduction of small signals in a manner that mimics nature, by the stochastic resonance phenomenon [20][21][22][23][24] . However, high fluctuation power, far above the fluctuations present at room temperature needs to be applied to achieve stochastic switching.…”
mentioning
confidence: 99%